A chapter on prophylactic democracies and a proposal - Cruz Apaza, Rodrigo R. (2024)
Democracy has as its fundamental pillars, among other nuclear assumptions, the freedom of expression and the rights of political participation, principles that enable the circulation and peaceful competition of ideas and the assumption of governmental power in the State. However, due to their broad contents, these are susceptible to collision with other goods of constitutional scope (principles, values and rights); the ramifications of the unrestricted use of these rights have been of such depth in some States since the 30s of the last century, that a series of constitutional and legal measures were arranged to fight and reduce the reproduction of errors or historical affections. We will call the democracies that adopted this profile of custodian prophylactic democracies, modalities of democratic organization that certain States instituted to protect themselves from devices that could cause their autolysis and that constitute, in our case, the object of investigation as a prelude to the formulation of a proposal for the Plurinational Republic of Bolivia.